EFFECTS OF ARTEMIA NAUPLII AND FORMULATED DIET ON GROWTH AND SURVIVAL OF LARVAE AND POST LARVAE OF CLARIAS GARIEPINUS( L).: Life Science-Zoology - C G ACHIONYE-NZEH; OLUMUJI K; BELLO N (International Journal of Life Science and Pharma Research, 2012)
The growth and survival of larvae and post larvae of Clarias gariepinus fed Artemia nauplii and formulated diet were investigated for a period of 50 days. A total of 2000 Clarias gariepinus larvae (mean weight 0.001 g) were randomly stocked into four tanks, with replicates, and fed on the 4th to 25th day after hatching with A. nauplii. They were fed 0.25% and 0.5% of their body weight with A.nauplii. Post larvae of C.gariepinus were fed from the 26th to the 50th day with 0.25% and 0.5% of formulated diet. The specific growth rate, survival, condition factor and mortality were calculated. Results indicated that there was increase in body weight; the mean was 0.042g for larvae fed 0.25 % and 0.057g for larvae fed with 0.5% of body weight respectively. Survival rate was high (95%). The specific growth rate was 6.41 % ± 1.59 for post larvae fed 0.25% and 9.35% ± 0.049 for post larval stage fed 0.5% of formulated diet. Specific growth rate was higher in larvae than post larvae. A.nauplii was a good starter live food for the larvae of C.gariepinus. By gradual replacement of A.nauplii, C.gariepinus larvae can be successfully weaned to formulated diet.